2006
DOI: 10.1097/01.brs.0000218072.25964.a9
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of a Novel Classification System for Thoracolumbar Injuries: The Thoracolumbar Injury Severity Score

Abstract: The TLISS has good reliability and compares favorably to other contemporary thoracolumbar fracture classification systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
1
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(82 citation statements)
references
References 27 publications
2
69
1
10
Order By: Relevance
“…16 Although as a whole it had an excellent construct validity, interobserver agreement for injury mechanism was only fair (kappa = 0.33). [17][18][19] This led to introduction of the Thoracolumbar Injury Classification and Severity Score (TLICS) in which fracture mechanism was replaced by description of morphological injury. 20 Others have pointed out some inherent limitations even in the recent TLICS classification system.…”
Section: Introductionmentioning
confidence: 99%
“…16 Although as a whole it had an excellent construct validity, interobserver agreement for injury mechanism was only fair (kappa = 0.33). [17][18][19] This led to introduction of the Thoracolumbar Injury Classification and Severity Score (TLICS) in which fracture mechanism was replaced by description of morphological injury. 20 Others have pointed out some inherent limitations even in the recent TLICS classification system.…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis also corroborates the results for the reliability of the TLICS/TLISS classification, as excellent results were obtained in regard to agreement between the treatments indicated by the classification and the treatment indicated by the evaluating surgeons, as previously demonstrated in various publications. 10,7,8,12,14,15 We attribute the findings of our study to the fact that the new classification was well established before the case analysis. In addition to receiving the original article and a summary version in Portuguese a week earlier, on the day of the evaluation, the surgeons attended an oral presentation about the TLICS system and received an explanatory summary about it.…”
Section: Discussionmentioning
confidence: 74%
“…And a small addition was included: in compression fractures, just as a burst fracture increases the score by a point, an angulation of more than 15 degrees in the coronal plane is assigned an additional point. Vaccaro et al, 10 in a study of seventy-one cases with five evaluators using the TLISS system, reported mild interobserver agreement for this classification.…”
Section: Discussionmentioning
confidence: 99%
“…2,8,9 Burst-type fractures may be present in up to 60% of these patients, 8,9 with a greater incidence of fractures in the thoracolumbar segment of the spine. [10][11][12] The same correlations were observed in the present study.…”
Section: Discussionmentioning
confidence: 99%